Household fuel use and migraine among Chinese adults aged 45 years and older: The modifying effects of sleep - Jiamin Yan; Xiaomei Wang; Bangxian Ding; Minzhe Zhang; Qiqiang He; Ye Zeng; Yun Xiang (PLoS ONE, 2025)
Background Various studies have established a link between household fuel use and diverse health conditions. However, research examining the impact of household fuel use on migraine remains scarce. Therefore, the objective of this study was to explore the association between household fuel use and the risk of migraine, as well as the potential modifying effects of sleep duration. Methods Utilizing a nationwide representative cohort from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2015, we included 9,160 participants aged 45 years and older who did not have migraine at baseline. Household fuel use was categorized into two groups: clean fuel and solid fuel. Migraine was defined based on self-reports using the ID-Migraine questionnaire. Sleep duration was classified into two groups: Non-ideal sleep duration (<7 hours/d or >8 hours/d) and ideal sleep duration (7–8 hours/d). Cox proportional hazards regression models were utilized to assess the associations of solid fuel use and sleep duration with migraine. The modifying effect of sleep duration was analyzed. Result During a 4-year follow-up period, 520 migraine cases were identified. The use of solid fuels was associated with an increased risk of migraine compared to the use of clean fuels. The hazard ratio (HR) and 95% confidence interval (CI) was 1.34 (1.06–1.69) for heating and 1.29 (1.06–1.58) for cooking with solid fuels, compared to the use of clean fuels. The use of solid fuels for heating and cooking simultaneously was also associated with an elevated risk of migraine (HR: 1.53, 95% CI: 1.16–2.01), compared with the simultaneous use of clean fuels. Additionally, compared with consistent solid fuels users, those switching from solid to clean fuel and consistently using clean fuels for heating and cooking showed a decreased risk of migraine. For heating, the HR was 0.66 (95% CI: 0.49–0.90) for switching from solid to clean fuel and 0.54 (95% CI: 0.38–0.77) for consistently using clean fuels; for cooking, the corresponding HRs were 0.74 (95% CI: 0.57–0.97) and 0.68 (95% CI: 0.53–0.86), respectively. Ideal sleep duration modified the association between solid fuel use and migraine. Among individuals with non-ideal sleep duration, the use of solid fuels for heating (HR: 1.47, 95% CI: 1.09–1.97, P = 0.010) and cooking (HR: 1.31, 95% CI: 1.02–1.68, P value = 0.034) was significantly associated with an increased risk of migraine. In contrast, these associations were not statistically significant among those with ideal sleep duration (heating: HR: 1.13, 95% CI: 0.77–1.65, P = 0.537; cooking: HR: 1.28, 95% CI: 0.90–1.81, P = 0.165). Conclusion Household solid fuel use was associated with an increased risk of migraine, and this association was modified by ideal sleep duration. Reducing exposure to household air pollution from solid fuel use and promoting healthy sleep behaviors may help to reduce the burden of migraine in areas where solid fuel use is prevalent.